2021
DOI: 10.1121/10.0006734
|View full text |Cite
|
Sign up to set email alerts
|

First characterization of vocalizations and passive acoustic monitoring of the vulnerable African manatee (Trichechus senegalensis)

Abstract: Even among the understudied sirenians, African manatees (Trichechus senegalensis) are a poorly understood, elusive, and vulnerable species that is difficult to detect. We used passive acoustic monitoring in the first effort to acoustically detect African manatees and provide the first characterization of their vocalizations. Within two 3-day periods at Lake Ossa, Cameroon, at least 3367 individual African manatee vocalizations were detected such that most vocalizations were detected in the middle of the night … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Currently, there are no published studies investigating if there are differences in frequency and temporal parameters among calf species. A few studies compared vocalizations between West Indian 33 and African manatee species 34 and noted significant overlap in frequency and temporal parameters. Although these differences were observed, it is unclear if calls from the West Indian and African manatees were obtained from adults and/or calves.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are no published studies investigating if there are differences in frequency and temporal parameters among calf species. A few studies compared vocalizations between West Indian 33 and African manatee species 34 and noted significant overlap in frequency and temporal parameters. Although these differences were observed, it is unclear if calls from the West Indian and African manatees were obtained from adults and/or calves.…”
Section: Introductionmentioning
confidence: 99%
“…All surveys were conducted between 06:00 and 10:00 AM, a timeframe during which manatees are more likely to be visually spotted in Lake Ossa (Takoukam Kamla, 2012). According to Rycyk et al (2021), African manatees in Lake Ossa seem to be more active out of daylight hours, presumably in avoidance of human presence. For all survey methods, detections were scored as presence/absence for each one-hour survey.…”
Section: Experimental Designmentioning
confidence: 99%
“…In addition, manatees produce a variety of vocalizations including squeaks, screeches, whines, and trills (Umeed et al, 2018;Brady et al, 2020;Baotic et al, 2022) shown to be important for their underwater communication and emitted across various behavioral states (Bengtson and Fitzgerald, 1985;O'Shea and Poche, 2006;Brady et al, 2021). Passive acoustics have been used in many studies to monitor manatees and have yielded up to 100% detection frequencies (LaCommare et al, 2008;Kikuchi et al, 2013;Rivera Chavarria et al, 2015;Rycyk et al, 2021;Rycyk et al, 2022). While the above methodologies have been used to monitor other species of manatee (Florida manatees: Rycyk et al, 2022;Antillean manatees: Ramos et al, 2020), they have been rarely implemented with African manatees.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies suggest that all Sirenian species make squeaks (referred to as chirp-squeaks in dugongs) that vary slightly in their range of f 0 (Anderson & Barclay, 1995;Nowacek et al, 2003;Rycyk et al, 2021;Sousa-Lima et al, 2008). West Indian manatees, African manatees, and dugongs produce vocalizations with overlapping f 0 ranges from 0.5 to 5 kHz (Anderson & Barclay, 1995;Nowacek et al, 2003;Rycyk et al, 2021), whereas Amazonian manatees produce calls with a higher f 0 at 1.6 to 8 kHz (Sousa-Lima et al, 2008). The other common vocalization described in the dugong and manatees is the atonal vocalization.…”
Section: Structure and Function Of Vocalizationsmentioning
confidence: 99%